The flexible surface revisited: Adsorbate-induced reconstruction, homocoupling, and sonogashira cross-coupling on the Au(100) surface - Feria Hernandez, L. (2017)
Phenylacetylene (PA) and iodobenzene (IB) are prototypical reactants in Sonogashira cross-coupling. Their adsorption behavior and reactivity on the Au(100) surface were studied by STM, temperature-programmed desorption and reaction, and DFT calculations that included the effect of dispersion forces. The two species exhibited very different behavior. Thus, even at 200 K, PA rearranged Au surface atoms so as to lift the hex reconstruction and adsorb in 4-fold-symmetric islands on the unreconstructed 100 surface. On the other hand, IB adsorbed on the reconstructed hex surface, again as islands, forming three different coexisting close-packed structures. The DFT results are in good accord with these findings, demonstrating the strong preference of PA and IB for the (100) and hex surfaces, respectively. Moreover, the calculated adsorption energies were in satisfactory agreement with values estimated from the desorption data. Adsorbed separately, both PA and IB underwent homocoupling, yielding diphenyl diacetylene and biphenyl, respectively; in the former case, reaction appeared to originate at island boundaries. On the well-annealed surface, coadsorbed PA and IB behaved independently, generating only products of homocoupling. However, on the Ar+ roughened surface, Sonogashira cross-coupling also occurred, yielding diphenyl acetylene. These findings are discussed in terms of the island-forming propensity of the reactants, amplified by the labile nature of the Au 100 surface under adsorption and the marked preference of the two reactants for different substrate structures, factors that act to inhibit the formation of a mixed adlayer and suppress reactivity. The implications for the behavior of practical Au nanoparticle catalysts are considered